Improvement of physical training of young weightlifters in microcycles at the initial stage - Mavropulo O.S. ,; Trufanova S.N. ,; Zavodnyi N.A. ,; Odintsova V.I. ,; Chub S.A. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to increase the efficiency of physical training of young weightlifters in microcycles at the initial stage with the predominant use of the circular training method. Methods and structure of the study. Classes in the control group were held in accordance with the approved program of initial training in weightlifting for 2023-2024, and in the experimental group, mainly using exercises using the circuit training method. Results and conclusions. Wave-like alternation and gradual increase in load from cycle to cycle and from session to session within a cycle formed the basis of training for young athletes from the experimental group, which ultimately contributed to an increase in the level of physical fitness. Thus, the presented method and means of circular training in theoretical significance can be recommended for inclusion in the general base of the training system in weightlifting for the development of training plans for physical training at the initial stage in order to increase the effectiveness of training in microcycles of young weightlifters.